2022
DOI: 10.22146/jcef.2878
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Early Warning System Based on Maritime Wireless Communication

Abstract: Tsunami buoy, linked to satellite, is commonly used as a tsunami early warning system but has been discovered to have several drawbacks such as the need for approximately 5 minutes to issue an early warning for a tsunami after detecting the initial wave as well as its fragility. It was also reported that the twenty-two buoys placed in the Indonesian seas from 2012 to 2018 were damaged and missing. Therefore, this study proposes a new method for tsunami early warning by integrating ship-to-ship maritime wireles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…A study in [6] used a particle swarm optimization algorithm and a 2D nonlinear equation to place the sensor to reduce the detection time. The authors found an inverse relation between tsunami detection time and the number of sensor nodes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in [6] used a particle swarm optimization algorithm and a 2D nonlinear equation to place the sensor to reduce the detection time. The authors found an inverse relation between tsunami detection time and the number of sensor nodes.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, New Zealand has a DART sensor system of 12 sensors, which is further connected to other global partners for the real transmission of data [5]. Although using satellites is one of the commonly used technologies for tsunami detection, it can take up to five minutes to issue an early warning after tsunami detection [6].…”
Section: Introductionmentioning
confidence: 99%